Health management committee strengthening and community mobilisation through women's groups to improve trained health worker attendance at birth in rural Nepal: a cluster randomised controlled trial - Joanna Morrison; Kirti Tumbahangphe; Aman Sen; Lu Gram; Bharat Budhathoki; Rishi Neupane; Rita Thapa; Kunta Dahal; Bidur Thapa; Dharma Manandhar; Anthony Costello; David Osrin (BMC, 2020)
Abstract Background Engaging citizens and communities to make services accountable is vital to achieving health development goals. Community participation in health management committees can increase public accountability of health services. We conducted a cluster randomised controlled trial to test the impact of strengthened health management committees (HMCs) and community mobilisation through women's groups on institutional deliveries and deliveries by trained health workers in rural Nepal. Methods The study was conducted in all Village Development Committee clusters in the hills district of Makwanpur (population of 420,500). In 21 intervention clusters, we conducted three-day workshops with HMCs to improve their capacity for planning and action and supported female community health volunteers to run women's groups. These groups met once a month and mobilised communities to address barriers to institutional delivery through participatory learning and action cycles. We compared this intervention with 22 control clusters. Prospective surveillance from October 2010 to the end of September 2012 captured complete data on 13,721 deliveries in intervention and control areas. Analysis was by intention to treat. Results The women's group intervention was implemented as intended, but we were unable to support HMCs as planned because many did not meet regularly. The activities of community based organisations were systematically targeted at control clusters, which meant that there were no true 'control' clusters. 39% (5403) of deliveries were in health institutions and trained health workers attended most of them. There were no differences between trial arms in institutional delivery uptake (1.45, 0.76-2.78) or attendance by trained health workers (OR 1.43, 95% CI 0.74-2.74). Conclusions The absence of a true counterfactual and inadequate coverage of the HMC strengthening intervention impedes our ability to draw conclusions. Further research is needed to test the effectiveness of strengthening public accountability mechanisms on increased utilisation of services at delivery. Trial registration Current Controlled Trials ISRCTN99834806 . Date of registration:28/09/10.